Knowing Your Beans in Parkinson’s Disease: A Critical Assessment of Current Knowledge about Different Beans and Their Compounds in the Treatment of Parkinson’s Disease and in Animal Models - Michel Rijntjes (Parkinson's Disease)
This review contains a critical appraisal of current knowledge about the use of beans in both animal models and patients with Parkinson’s disease (PD). The potential beneficial effects of beans in PD are increasingly being touted, not only in scientific journals but also by the lay media. While there is a long tradition in Ayurvedic medicine of prescribing extracts from Mucuna pruriens (MP), whose seeds contain 5% L-3,4-dihydroxyphenylalanin (L-DOPA), many other beans also contain L-DOPA (broad beans, common beans, and soybeans) or have other ingredients (coffee and cocoa) that may benefit PD patients. Indeed, bean-derived compounds can elicit neuroprotective effects in animal models of PD, while several studies in human PD patients have shown that motor performance can improve after ingestion of bean extracts. However, there are several arguments countering the view that beans serve as a natural therapy for PD: (i) the results from animal PD models are not necessarily directly applicable to humans; (ii) beans have many bioactive ingredients, some of which can be harmful in large doses; (iii) studies in human PD patients are scarce and only report on the effects of single doses or the administration of bean extract over short periods of time; and (iv) no data on long-term efficacy or side effects of bean therapy are available. Therefore, reservations about the use of beans as a “natural” therapy for PD seem to be justified.